2015
DOI: 10.1097/mbp.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

Validation of inflationary noninvasive blood pressure monitoring in the emergency room

Abstract: ObjectiveThe aim of this study was to compare the values of a noninvasive blood pressure (NIBP) measurement during cuff inflation (inflationary NIBP) and deflationary NIBP measurements and to verify whether inflationary NIBP is equivalent to conventional deflationary NIBP and is acceptable for clinical use in the emergency room (ER).Materials and methodsA total of 2981 NIBP data points were collected from 175 patients (age, 56.5±22.2 years; range, 7–92 years) who had been treated in the resuscitation area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…We hypothesized that, compared with the conventional NIBP monitoring device, the iNIBP would measure the blood pressure faster, particularly when the blood pressure has suddenly increased or decreased. There have been two observational studies on the use of the iNIBP [3,4], but no studies on the accuracy of the iNIBP.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that, compared with the conventional NIBP monitoring device, the iNIBP would measure the blood pressure faster, particularly when the blood pressure has suddenly increased or decreased. There have been two observational studies on the use of the iNIBP [3,4], but no studies on the accuracy of the iNIBP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an ideal inflation procedure should include adjusting the speed of the air-pump to keep the pressure stable when different cuffs are used. To date, only two inflation procedures have been developed: one by Welch Allyn SureBP [ 2 ], and one by Nihon Kohden Corporation [ 6 , 7 ]. Mindray TrueBP is a novel non-invasive BP measurement algorithm based on inflation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While the study results demonstrated the utility of iNIBP monitoring during anaesthesia induction, for 10% of the measurements, the iNIBP mode switched to the dNIBP mode. Previous studies have reported that body motion and arrhythmia might affect determination of the measurement method (Sasaki et al 2015). We hypothesised that acute changes in blood pressure might affect the measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (Onodera et al 2011) showed that BP could be determined by the iNIBP mode in 13.0 ± 2.3 seconds, whereas it took 32.7 ± 13.6 seconds to determine BP by the conventional dNIBP mode under stable haemodynamic conditions. On the other hand, iNIBP monitoring automatically switches its measurement mode to the dNIPB mode in certain situations, including during acute blood pressure changes, arrhythmias, body motion or patient interaction with the cuff, resulting in delayed BP measurement (Sasaki et al 2015).…”
Section: Introductionmentioning
confidence: 99%